Identification of Learning Experience in Online Learning with User Persona Techniques Based on Learner-Centered Design Concepts - Putu Yudia Pratiwi; I Gede Sudirtha (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
Online learning is now not a new thing in the world of education. However, with the change in the learning system that is carried out entirely online, of course, there is a need for adjustments so that the quality of learning is maintained. Online learning has provided convenience in the learning process because it can be done asynchronously. Understanding the learning experience of students is very important to optimize learning that focuses on learner-certified design. A good learning experience will also have an impact on student learning outcomes. Therefore, it is necessary to identify and analyze the needs of students in online learning so that the learning process becomes more optimal. The use of persona techniques can provide more detailed information to explore the needs of students in the online learning process. This research begins by identifying problems, observing target users, persona design, and persona analysis. The results of the study indicate that there are several shortcomings and obstacles faced during online learning and several things that need to be considered for online learning in the future, namely lectures to be carried out according to a predetermined schedule, providing more reference materials and more detailed explanations of material, providing learning videos for providing additional understanding related to lecture material, provide quizzes and discussion forums on e-learning at the end of each material, more intense interaction is needed to discuss learning materials, more frequent online meetings are held to provide confirmation and discussion of material and provide feedback on each assignment.